Cost-effectiveness of Apixaban for Stroke Prevention in Patients with Atrial Fibrillation in Algeria - Yazid Aoudia; Thitima Kongnakorn; Evie Merinopoulou; Mohamed Said Bettayeb; Sid Ahmed Kherraf (Journal of Health Economics and Outcomes Research)
**Background:** Atrial fibrillation (AF) is a chronic sustained heart rhythm disorder associated with an increased risk of stroke. Apixaban, a new oral anticoagulant, was approved by the European Medicines Agency for prevention of stroke in patients with AF. The efficacy of apixaban has been investigated in randomised controlled trials.